Hypsilara breweri n.sp. from Venezuela: description of new species with notes on the morphology and phylogenetic relationships of the genus (Coleoptera: Elmidae: Larainae) - Čiampor, Fedor Jr; Laššová, Kristína; Čiamporová-Zaťovičová, Zuzana (Zootaxa, 2013)
A new species of the genus Hypsilara Maier & Spangler, 2011, collected in the Eastern Venezuela, is described and illus-trated. We provide habitus photographs, detail drawings of both male and female genitalia, and description of some mor-phological features, which were omitted in the description of the genus. Included are also remarks on the distribution and genetic distance of the Hypsilara species and possible relations to other South American Larainae.